(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Renal stone formation and the predominant chemical stone composition are age and gender dependent. The most common stones are struvite (magnesium ammonium phosphate), calcium oxalate, urate, cystine and silica. The most common type of kidney stones worldwide contains calcium. The process of forming stones in the kidney, bladder, and/or urethra (urinary tract) is called as Urolithiasis. Urinary calculi may cause obstruction, hydronephrosis, infection and hemorrhage in the urinary tract system. Citrus species were used in traditional practices as remedies for the urolithiasis have been well established in vivo-vitro test, clinical trial and effective use but are lacking well documented record. Citrus limon (L.) is tree with evergreen leaves and yellow edible fruits from the family Rutaceae. Citrus aurantiumL commonly called as bitter orange. Citrus medica Linn.,commonly known as a Citron in English and bijapura in Ayurvedic literature is shrub or small tree. All three are reported to use in treatment of wide panel of diseases like antiurolithic activity, stomach ache, vomiting antifungal and antibacterialetc. Urolithiasis was introduced by administration of ethylene glycol in rats. Standard drug treated group, the urinary outputs increased significantly. Body weight of all animals measured on day 0, 14 and 28 of calculi induction to assess the effect of treatment on body weight. The collection of urine from rats scheduled to be every seven days from calculi induction. C. aurantinum extract showed significantly increase in urinary output. The collected urine stored in 4ºC. The analysis of calcium, phosphate, magnesium, creatinine, uric acid, protein, urea nitrogen and oxalate recorded.300 mg/kg of combined extract of all three plants show significant result compare to individual plant response.